2016
DOI: 10.1097/inf.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C

Abstract: Cystatin C values were associated with GFR and β-2-microglobulin. Cystatin C may be useful as a marker of renal function in HIV-infected pediatric patients, independently of ongoing inflammation or viremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…These findings accorded with our observations of cystatin C levels and COVID-19. Of note, a multicenter cohort study of pediatric subjects infected by human immunodeficiency viruses (HIV) demonstrated that cystatin C levels were strongly related to kidney function and inflammatory state [ 34 ]. Positive relevance of elevating cystatin C levels to plasma HIV RNA status was also observed in adult patients with HIV infection whose antiretroviral therapy was randomly interrupted [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings accorded with our observations of cystatin C levels and COVID-19. Of note, a multicenter cohort study of pediatric subjects infected by human immunodeficiency viruses (HIV) demonstrated that cystatin C levels were strongly related to kidney function and inflammatory state [ 34 ]. Positive relevance of elevating cystatin C levels to plasma HIV RNA status was also observed in adult patients with HIV infection whose antiretroviral therapy was randomly interrupted [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both cytokines have been increased in our experiment by CP, an action that was significantly antagonized by sesamin treatment. Cystatin, in addition to being a reliable renal biomarker in both acute kidney injury and chronic kidney disease (Ali et al 2018), is also considered a biomarker for inflammation (Deyà-Martínez et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the serum CysC, increased urinary CysC has been recognized as a marker of renal tubular dysfunction [ 65 ]. Urinary CysC concentration has been found to be increased in HIV subjects [ 42 ] and to correlate with GFR and B2-M in patients with HIV infection [ 66 ]. Urinary CysC/Cr also correlates with urinary RBP/Cr, suggesting that CysC may be better markers of specific forms of proximal tubular dysfunction in these patients [ 27 ].…”
Section: Cystatin Cmentioning
confidence: 99%
“…Urinary CysC/Cr also correlates with urinary RBP/Cr, suggesting that CysC may be better markers of specific forms of proximal tubular dysfunction in these patients [ 27 ]. It has been also suggested that CysC may be useful as a marker of renal function in HIV-infected patients, independently of ongoing inflammation or viremia [ 66 ].…”
Section: Cystatin Cmentioning
confidence: 99%